COMBATING SECOND HAND SMOKING WITH COMMUNITY PARTICIPATING ‘SMOKE FREE ZONES’: SRI LANKA EXPERIENCES - Prakash, Thambiliya Godage Supun Lahiru; Kumara, Samarawikrama Gamachchige Prasanna; Niwarthana, Humpita Pathirannehelage Geethani; Abeynayake, Turlin; Abeykoon, Palitha; Pallewaththa, Prabhath Wijitha Kumara (LIFE: International Journal of Health and Life-Sciences, 2018)
Although the overall smoking prevalence has shown a downward trend, second hand smoke (SHS) exposure remains a significant problem in Sri Lanka. Various attempts have been made to establish ‘Smoke Free Zones’ (SFZs) for combating SHS with the help of Public Health Inspectors (PHIs) who are regarded as the main coordinators of combating SHS at the grass root level. This study explored the lessons learnt from establishing SFZs in Sri Lanka and both qualitative and qualitative approaches were employed. There were 53 SFZs from 20 Districts that were studied, and the study consisted with three components. Chi – square test was performed to study the relationships between variables and qualitative data was analyzed through the framework analyzing method. All studied SFZs focused on reducing the availability of tobacco products by mobilizing retailers parallel to creating awareness among the stakeholders. The mean time taken to reach the maximum success is 9 (±8) months and mean sustained period is 16 (±12) months. Forty nine factors for establishing SFZs were identified and six factors have had statistically significant relationship with sustainability. Furthermore, ten constructive groups and twelve destructive groups as well as fifteen reasons for deteriorating the successes were encountered. Ten steps process for establishing SFZs in Sri Lanka was also Introduced. The study recommends employing the introduced 10 steps process to establishing SFZs in Sri Lanka and develops the strengths and opportunities while minimizing the weaknesses and threats to create a supportive environment prior to establishing SFZs and pay continuous attention on the reasons for deteriorating success to improve the sustainability.